The Innovation Landscape of Indonesian SNBFIs: Balancing Sharia Compliance and Market Competitiveness - Susi Widiati; Sumarta (Penerbit Hellow Pustaka, 2026)
This research aims to identify and analyze product innovation in Sharia Non-Bank Financial Institutions (SNBFIs) in Indonesia, including the mechanisms of driving factors, barriers, and their implications for the industry's competitiveness and sustainability. This study employs a qualitative approach with a library research design, analyzing various scientific literatures, industry reports, and relevant policy documents. The findings indicate that the driving mechanisms for innovation include increasingly diverse customer needs, industrial competitive pressures, and rapid advancements in digital technology. A prominent form of innovation identified is the development of Sharia micro-insurance (micro-takaful), which is affordable for low-income communities, as well as the utilization of Sharia crowdfunding platforms for MSME financing based on Sharia contracts. Conversely, product innovation faces several barriers, particularly regarding regulatory and resource aspects. The Sharia compliance process, which requires fatwa validation, is often time-consuming, compounded by a shortage of human resources proficient in both fiqh muamalah and technology, and limited funding for research and development. Furthermore, regulatory rigidity in the early stages of innovation poses a significant challenge for new product development. This study affirms that product innovation is a strategic necessity for SNBFIs to enhance competitiveness and expand Sharia financial inclusion. Therefore, synergy among institutions, regulators, and the digital ecosystem is required to create adaptive, inclusive, and Sharia-compliant innovations.